The Application of the Mind Mapping Cooperative Learning Model to Improve Learning Outcomes of Islamic Religious Education on the Fathu Makkah Material in Elementary School - Ina Marlina; Aam Amaliyah (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Learning outcomes in Islamic religious education, particularly on the topic of Fathu Makkah, remain suboptimal because classroom instruction is often teacher-centered, which limits student motivation and active engagement. Objective: This study aims to analyze the effectiveness of the Mind Mapping cooperative learning model in improving learning outcomes, motivation, and student engagement among fifth-grade elementary school students. Method: The study utilizes a Classroom Action Research design based on the Kemmis and McTaggart model, conducted in two cycles, encompassing planning, action implementation, observation, and reflection. Data were collected through learning achievement tests, motivation questionnaires, observations, and documentation, and were subsequently analyzed quantitatively and qualitatively using a descriptive approach. Results: The findings show that the average student score increased from 75 to 85, learning mastery improved from 60% to 90%, motivation scores increased from 3.2 to 4.5, and student engagement increased from 70% to 85%. Conclusion: The Mind Mapping cooperative learning model effectively enhances learning outcomes, motivation, and student engagement. Contribution: This study provides empirical evidence that Mind Mapping supports active, collaborative, and student-centered Islamic religious education learning in elementary schools.